Experimental and Theoretical Acoustic Performance of Esparto Grass Fibers - Rubén Maderuelo-Sanz; Juan Miguel Meneses-Rodríguez (Acoustics)
Nowadays, natural fiber-based materials are widely used in the building sector, where the use of green and sustainable products is of growing interest. One of these fibrous materials is the esparto, a plant belonging to the Gramineae family, with a height up to 1 m. It grows in arid places with scarce rainfall, being common in some areas of the Iberian Peninsula. Due to its morphology, it can be used to replace conventional materials used in soundproofing and building applications. In this work, the acoustic properties of esparto fibers are studied using impedance tube measurements and via a phenomenological acoustic model where the input parameters are some non-acoustic properties such as porosity, density, tortuosity, and flow resistivity. The experimental results obtained showed the good acoustic performance of esparto fibers, with a high sound absorption coefficient along the usual frequency bandwidth. Furthermore, the theoretical results obtained using the phenomenological model exhibited a strong correlation with the sound absorption spectra obtained through experimental measurements.